(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2025)
This dissertation investigates how Uzbekistan can ensure national economic stability by using state financial resources more effectively across fiscal, monetary, and customs policy instruments. Anchored in the priorities of the “Uzbekistan–2030” strategy, the study systematizes theoretical approaches, scrutinizes the country’s legal-regulatory framework, and evaluates practice across different stages of economic development. It argues that stability is strengthened when budget expenditures are disciplined and performance-oriented, tax and customs incentives are targeted and time-consistent, and monetary operations complement real-sector objectives. The research goal is to develop actionable proposals to raise the effectiveness of state financial resource use; tasks include mapping theory and law, assessing fiscal, monetary, and tariff channels, benchmarking international practices, and formulating priority scenarios for reform. Methodologically, the work applies grouping, comparative and economic analysis, and economic-mathematical modeling and forecasting.